Microsatellite instability is highly prevalent in older patients with colorectal cancer - Jakob, Daniel; Orth, Valerie; Gödde, Daniel; Zirngibl, Hubert; Ambe, Peter C. (Frontiers in Surgery, 2024)
Clinical guidelines suggest screening of colorectal cancer (CRC) for microsatellite instability (MSI). However, microsatellite instability -high (MSI-H) CRC is not rare in older patients. This study aimed to investigate the prevalence of MSI-H CRC in an unselected population in an age-based manner.A retrospective analysis of data from patients undergoing radical surgery for CRC was performed. Only cases with results from MSI testing using immunochemistry (IHC) were analyzed. Age-based analyses were performed using two cut-off ages: 50 years. as stated in Amsterdam II guidelines, and 60 years. as outlined in the revised Bethesda criteria.The study population included 343 (146 female and 197 male) patients with a median age of 70 years (range 21 -90 years). The prevalence of MSI-H tumors in the entire cohort was 18.7 %. The prevalence of MSI-H CRC was 22.5 % in the group less than or equal to 50 years vs. 18.2 % in the group > 50 years using the age limit in the Amsterdam II guidelines. MSI-H CRC was present in 12.6 % of the group aged less than or equal to 60 years compared to 20.6% in the control group > 60 years. MSI screening of CRC based on age alone is associated with negative selection of a relevant number of cases. MSI-H CRC is also common in elderly patients, who may be negatively selected secondary to an age-based screening algorithm. Following the results of this study, screening based on clinical criteria should be omitted in favor of systematic screening as is already internationally practiced.